2021
DOI: 10.1021/acs.nanolett.1c00064
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Fingerprint of Senescence in Endothelial Cells

Abstract: Endothelial senescence entails alterations of the healthy cell phenotype, which accumulate over time and contribute to cardiovascular disease. Mechanical aspects regulating cell adhesion, force generation, and the response to flow contribute to the senescence-associated drift; however, they remain largely unexplored. Here, we exploit force microscopy to resolve variations of the cell anchoring to the substrate and the tractions generated upon aging in the nanonewton (nN) range. Senescent endothelial cells disp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 63 publications
2
19
0
Order By: Relevance
“…Senescent endothelial cells fail to change shape in response to flow [ 37 ] and generate monolayers where the cell aspect ratio is unaffected, while the cell orientation remains randomly distributed despite the exposure to WSS ( Figure ). The functional decay of senescent cells was modeled by including particles that do not change shape in response to external fields in the in silico representation, which we term senescent particles.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Senescent endothelial cells fail to change shape in response to flow [ 37 ] and generate monolayers where the cell aspect ratio is unaffected, while the cell orientation remains randomly distributed despite the exposure to WSS ( Figure ). The functional decay of senescent cells was modeled by including particles that do not change shape in response to external fields in the in silico representation, which we term senescent particles.…”
Section: Resultsmentioning
confidence: 99%
“…The biological phenomenon of senescence subtends to the loss of endothelial cell adaptivity to flow. [ 37 ] Individual endothelial cells drift to functional decay, driven by the timely accumulation of genetic and metabolic damage. [ 24 ] This could lead to a progressive impairment of the collective response and functionality in tissues populated by a growing number of senescent cells.…”
Section: Discussionmentioning
confidence: 99%
“…All these mechanisms contribute to age-related hypertension. Chala et al, in an in vitro model of endothelial senescence, showed that endothelial cells have a reduced capacity to adapt to the local hemodynamic conditions [ 69 ] functionally. Interestingly, recent experimental studies showed that disturbed flow induces endothelial senescence.…”
Section: Endothelial Dysfunction and Impaired Angiogenesis In The Eld...mentioning
confidence: 99%
“…As mentioned, previous SCFS techniques did not produce a sufficient data output, and even low-cell-number SCFS studies suggested that the measured SCFS parameters do not follow a specific distribution. Namely, the maximal single-cell adhesion force ( F max ), adhesion energy ( E max ), and the traveled distance of the cantilever, with respect to the surface at F max ( D max ) were typically investigated 7 , 10 , 19 , 21 , 36 . Importantly, low throughput does not allow studying the distributions of large cell populations or revealing possible subpopulations.…”
Section: Introductionmentioning
confidence: 99%